On Totally (p,k) Quasiposinormal Operator - Senthilkumar, D.; Kiruthika, D. (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper we study some properties of totally (p,k) - quasiposinormal operator. And also we show that Weyl's theorem and algebraically Weyl's theorem holds for totally (p,k) -quasiposinormal operator.